Nutritional assessment in children with special needs: what can we measure?. (29th September 2015) - Hardy, J; Boyd, D; Campbell, S; Canoy, D; Vail, A; Kauffmann, L
Abstract : In a group of children with special needs, all of whom have moderate to profound learning difficulties, our study aimed to: (1) determine which nutritional measurements are possible and their reliability; (2) compare measured supine length with that calculated from segmental measurements; (3) assess agreement of calculated fat mass and fat free mass from skinfold and bioimpedance measurements. Method: The authors randomly selected non-standing and standing children, aged 3–19 years, from five specialist support schools. Conditions present in non-standing children included cerebral palsy, spina bifida and neuromuscular disease. Measurements included weight, height (supine length for non-standers), skinfold thickness, body circumference, bioimpedance, and segmental measurements (for non-standers). Measurements were taken twice (2–4 weeks apart) by one rater for non-standers, and for standing children, one rater assessed 10 children and another assessed 13 children (same rater assessed on both occasions). Analysis was by calculation of 95% limits of agreement. Results: 30 nonstanders (mean age 10.8 years) and 23 standers (12.4 years) participated. Height and weight were measurable in all standers. Supine length and weight in all but two and one non-standers. Skinfolds were measurable in 90–93% of non-standers and 48–91% of standers, compared with bioimpedance in 87% and 78%, respectively. Reasons will be discussed. Height and weight reliability was reasonable in standers (−1.7 to 1.1 cm; −1.8 to 1.6 kg) but poor for non-standers (−6.6 to 7.3 cm; −2.3 to 1.9 kg). Height estimated from knee height was only slightly more reliable: −6.4 cm to 5.9 cm. Reliability of fat mass from skinfolds was acceptable in non-standers (−2.5 to 1.7 kg) but worse for standers (−7.8 to 4.7 kg). Fat mass calculated from bioimpedance was slightly more reliable: −2.1 to 1.8 kg and −3.7 to 4.3 kg respectively). Reliability of fat free mass calculated from bioimpedance was −2.14 to 2.19 kg and −3.91 to 3.17 kg, respectively. Conclusion: Anthropometry and bioimpedance are feasible to do with moderately good reliability in most children with special needs, even among those who are not independently mobile. Some measures, such as skinfold thickness, can be challenging to obtain for some children. Bioimpedance could be used as a simple tool for assessing body composition.